Water Markets, Demand and Cost Recovery for Piped Water Supply Services : Evidence from Southwest Sri Lanka - Nauges, Celine; van den Berg, Caroline (World Bank, Washington, DC, 2012)
In many countries water supply is a service that is seriously underpriced, especially for residential consumers. This has led to a call for setting cost recovery policies to ensure that the tariffs charged for water supply cover the full cost of providing for the service. Yet, the question arises on how consumers will react to such price increases. The authors illustrate the impact of price increases on consumption of piped water through a study of the demand for water of piped and non-piped households using cross-sectional data from 1,800 households in Southwest Sri Lanka. The (marginal) price elasticity is estimated at -0.74 for households exclusively relying on piped water, and at -0.69 for households using piped water but supplementing their supply with other water sources, with no significant differences between income groups. Those households that depend on non-piped water sources have a time cost elasticity (as a proxy for price elasticity) of only -0.06. The authors discuss the implications of these results in terms of pricing policy.